G-Range: development and use of a beta global rangeland model - Boone, Randall B.; Conant, Richard T.; Hilinski, T.E. (Colorado State University, 2011)
In April of 2010, Drs. Mario Herrero and Philip Thornton of the International Livestock Research Institute contracted with Drs. Boone and Conant to create a global rangeland model of moderate complexity. Boone was funded for a 50 day effort, and Conant for ca. 40 days. An opportunity to prepare a manuscript for a special issue of the Proceedings of the National Academy of Science arose, and Conant took the lead in that effort. Boone created the rangeland model, called G-Range, with input from Conant, drawing upon existing models and new information (see Acknowledgements). Conant and Hilinksi reviewed the logic used in G-Range to simulate ecosystem processes, and joined to create the initial baseline simulation and conduct the scenario reported in this report. This report summarizes that effort, and provides guidance on using the accompanying simulation software. The structure of this report was influenced by the ODD (Overview, Design Concepts, and Details) protocol described in Grimm et al. (2006; 2010).